What drives researchers to engage in R&D contracts? - Olaya-Escobar, Erika Sofía (2021)
This article investigates the factors that shape researchers’ willingness to engage in university-industry R&D contracts. The case of the Universidad Nacional de Colombia is examined. These contracts allow students to work in real-life projects, in which a group of highly qualified academics confront theory and practice to generate solutions for the business sector, thus enriching traditional academic practices. The instrument used in this study consists of five dimensions: attitude towards KTT (knowledge and technology transfer) activities, expectation of contribution, promotion incentives, university culture and regulation, and supporting KTT services. The sample comprises 184 professors. The relevance of each factor related with the participation of researchers in R&D contracts (period 2010-2015) is identified through a structural equation model. The key findings emphasize the role played by culture and a favourable normative framework for KTT activities, while support services seem to negatively affect researchers' engagement in R&D contracts. Intrinsic and extrinsic motivations do not have a significant effect on the participation in R&D contracts.